2014
DOI: 10.21608/jfds.2014.53189
|View full text |Cite
|
Sign up to set email alerts
|

Using of Honey and Olive Oil in Production of Synbiotic Yoghurt

Abstract: The effect of fortification with both honey and olive oil on yoghurt quality was investigated. Control yoghurt was made using classic yoghurt culture and whole milk. Fou other yoghurt treatments were made by ABT culture and whole milk fortified with 0+0, 2+1, 4+2, and 6+4% of honey and virgin olive oil respectively. The sixth treatment was prepared using ABT culture and skim milk contained 6% honey + 4% virgin olive oil. Changes in rheological, chemical, microbial and organoleptic properties of yoghurt were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The other distinguishing characteristics of the sensory evaluation of the yoghurts with added oil were rated slightly worse by the panellists than the control yoghurts. The sensory quality analysis conducted by Ammar et al [52] for yoghurts with different levels of olive oil addition to probiotic yoghurts showed that the addition improved the ratings for texture, consistency, and flavour of fresh products, while after storage, these quality attributes were rated slightly worse. In contrast, a study by Barrantes et al [53] indicated that the addition of vegetable oils to yoghurt negatively affected the sensory quality evaluation of these products.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The other distinguishing characteristics of the sensory evaluation of the yoghurts with added oil were rated slightly worse by the panellists than the control yoghurts. The sensory quality analysis conducted by Ammar et al [52] for yoghurts with different levels of olive oil addition to probiotic yoghurts showed that the addition improved the ratings for texture, consistency, and flavour of fresh products, while after storage, these quality attributes were rated slightly worse. In contrast, a study by Barrantes et al [53] indicated that the addition of vegetable oils to yoghurt negatively affected the sensory quality evaluation of these products.…”
Section: Sensory Analysismentioning
confidence: 99%